2021
DOI: 10.1158/1078-0432.ccr-20-0557
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of miRNAs Identifies Clinically Relevant Epithelial and Stromal Subtypes of Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: The objective of this study is to characterize the role of miRNAs in the classification of head and neck squamous cell carcinoma (HNSCC).Experimental Design: Here, we analyzed 562 HNSCC samples, 88 from a novel cohort and 474 from The Cancer Genome Atlas, using miRNA microarray and miRNA sequencing, respectively. Using an integrative correlations method followed by miRNA expression-based hierarchical clustering, we validated miRNA clusters across cohorts. Evaluation of clusters by logistic regression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 56 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…All miR-200 members have been shown to play an important part in repressing malignant cell transformation and in inhibiting tumor initiation, and have thus been characterized as tumor suppressors [ 127 , 128 ]. More specifically, the miR-200 family has been reported to negatively modulate the progress of EMT in various cancers, including HNSCC [ 129 ], by controlling the expression of transcriptional repressors ZEB1 and ZEB2, the so-called EMT master regulators [ 126 , 130 , 131 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…All miR-200 members have been shown to play an important part in repressing malignant cell transformation and in inhibiting tumor initiation, and have thus been characterized as tumor suppressors [ 127 , 128 ]. More specifically, the miR-200 family has been reported to negatively modulate the progress of EMT in various cancers, including HNSCC [ 129 ], by controlling the expression of transcriptional repressors ZEB1 and ZEB2, the so-called EMT master regulators [ 126 , 130 , 131 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…Although a significant progress on the pathogenesis of HNSCC has been made in the past decades, the exact molecular mechanisms are still not well understood. Increasing evidences implicates that dysregulation of miRNAs has a critical role in the development and progression of HNSCC (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…One of the predicted targets of miR-203a in our analysis was Semaphorin 5a that is associated with lymph node metastasis and adverse prognosis [ 58 ]. Integrative Analysis of miRNAs in HNSCC has previously identified miR-194 to be associated with the epithelial sub-type of HNSCC [ 59 ]. However, to the best of our knowledge no study has shown the role of miR-203, miR-194 and miR-10a as a prognostic indicator of LVI in HNSCC.…”
Section: Discussionmentioning
confidence: 99%